DEVELOPING MATHEMATICS QUESTIONS OF PISA TYPE USING BANGKA CONTEXT - M Noviarsyah Dasaprawira; Zulkardi Zulkardi; Ely Susanti (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2019)
This study aims to develop a math problem type PISA to familiarize students using problems with PISA standard and produces a valid, practical, PISA context of Bangka (Tanjung Kalian Lighthouse) type and see the basic math skills (KDM) seen from the context of Tanjung Kalian lighthouse. The research method used is design research with the type of research development or development studies. The result of the research is a valid PISA math problem at the expert review stage and one to one, while small group stages do the practicality. The ability that is found in the form of communication, representation, mathematical, reasoning, and argument, and formulates a strategy to solve the problem.